Ocular health in professionals in charge of analysing blades in laboratory - Cristiana Brasil de Almeida; Lorita Marlena Freitag Pagliuca (Rev Rene)
Visual perception is used in laboratory work and may expose professionals to ocular system occupational risk. One aimed at: evaluating ocular health, identifying occupational risks and proposing eye care. This study was exploratory, descriptive and quantitative. Sample was of 42 professionals in charge of analyzing blades in laboratory at the cytology sector of a public institution, divided into a group composed of people from 20 to 40 years-old and another one composed of people up to 40 years-old. Evaluation involved the exam of external structures and of visual capacity. Analysis took into account health/disease background, problems identified in the ocular exam and working conditions. In the working area one could notice that there were no stimulation objects for visual rest. In the external exam one detected eye burning, hiperemi conjunctivis, bleeding points, pterygium and convergent strabismus. Concerning visual accuracy: regular or satisfactory vision (13), below the average (10) and non-satisfactory vision (19). It is important the evaluation of these workers regularly and their work environment as well.